Preparation, assessment, and comparison of α-chitin nano-fiber films with different surface charges. - Zhang, Yan.; Jiang, Jie.; Liu, Liang.; Zheng, Ke.; Yu, Shiyuan.; Fan, Yimin. (2016)
Abstract: Chitin nano-fibers with positive and negative charges have been, respectively, produced from partially deacetylated and 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidized α-chitin. The average diameters and lengths of the TEMPO-oxidized chitin nano-fibers (TOChN) were 14 ± 4.3 and 190 ± 140 nm, respectively, and the average diameters and lengths of the partially deacetylated chitin nano-fibers (DEChN) were 6 ± 1.7 and 320 ± 105 nm, respectively. A partially deacetylated chitin nano-fiber film (DEChN-F), a TEMPO-mediated and oxidized chitin nano-fiber film (TOChN-F), and a composite film (DE-TO-ChN-F) consisting of a combination of the two were prepared by drying the dispersions at 40 °C. The DEChN-F, TOChN-F, and DE-TO-ChN-F all have similar tensile strengths of approximately 90 MPa; however, the chitosan film (Chitosan-F) had a tensile strength of approximately 30 MPa. In addition, TOChN-F and DE-TO-ChN-F have a thermal weight loss at 210 °C, and DEChN-F has a thermal weight loss at 280 °C. DEChN-F was found to have antimicrobial activity with regards to Escherichia coli. Finally, the chitin nano-fiber films could be slightly degraded by cellulase, which provided a novel biological performance of the chitin nano-material.; Keywords: Chitin, Nano-fiber, Films, Antimicrobial activity, Enzymatic degradation.; Springer Open.